2013
DOI: 10.1103/physrevb.88.144412
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of the tensile-strain-induced tetragonal state of SrRuO3films

Abstract: SrRuO 3 films have been grown in the tetragonal, structurally single-domain state under 1% of biaxial tensile strain. The angular dependencies of the magnetization and the magnetoresistance reveal an upright orientation of the tetragonal unit cell and biaxial magnetic in-plane anisotropy with 110 t easy axes. Reversible biaxial strain from piezoelectric Pb(Mg 1/3 Nb 2/3 ) 0.72 Ti 0.28 O 3 (PMN-PT) substrates has been applied to probe the direct strain response of the magnetization and the electrical resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…In addition, the lattice constant and on-site energy of Ti play an important role in this magnetic metal-insulator transition. More importantly, our results agree well with the experimental findings in which tensile strain can affect the Curie temperature in SRO thin film [51,52].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the lattice constant and on-site energy of Ti play an important role in this magnetic metal-insulator transition. More importantly, our results agree well with the experimental findings in which tensile strain can affect the Curie temperature in SRO thin film [51,52].…”
Section: Discussionsupporting
confidence: 91%
“…For U Ru = 3.5 eV and U Ti = 5.0 eV (square), the T MF C decreases with increasing λ, similar to previous conclusions of the lattice effect on the SRO magnetic phase (cf. [51,52]). Precisely for λ = 0, the J 1 2.53 meV and T MF C 39.2 K. However, with λ = 1, as described in the previous paragraph, the energy difference between FM and AFM phases becomes fairly small and the T MF C is only 0.5 K with J 1 0.059 meV.…”
Section: Monolayer Sro In Sro/sto Superlatticementioning
confidence: 99%
“…Similar to the orthorhombic phase, compressive strain causes a lower residual resistivity ratio. The observations described above are associated with the deformation rather than the tilting of RuO 6 octahedra and thus the change in effective correlation [90][91][92][93].…”
Section: Epitaxymentioning
confidence: 93%
“…Along with its electrode applications, due to its high metallicity upon ferromagnetic ordering, strain engineering of SrRuO 3 has become a popular research topic among thin-film scientists. Later, it has been found that the structural, metallic, and magnetic properties of SrRuO 3 thin films are highly sensitive to the substrate-induced strain (Figure 12a) [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: A Highly Conductive Ferromagnetic Metal: Srruomentioning
confidence: 99%
“…11 The lattice degree of freedom in SRO films has been identified as the main factor to modify their physical properties by using external fields. For example, Herklotz et al 12 and Zhou et al 13 in situ imposed an in-plane compressive strain to SRO films epitaxially grown on the ferroelectric Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 single crystals via the piezoelectric response and achieved lattice strain-mediated electric-field control of magnetic and electrical properties. In addition, SRO exhibits a striking dynamic visible-light-induced lattice variation, which arises from the non-equilibrium photopopulation.…”
mentioning
confidence: 99%